IMPLEMENTASI MODIFIKASI KURIKULUM PADA MATA PELAJARAN IPA DI SEKOLAH DASAR INKLUSI (STUDI PADA SISWA KELAS VI SD 1 TRIRENGGO BANTUL) - Natalia, Deswita; Nisa, Ana Fitrotun (Universitas Sarjanawiyata Tamansiswa, 2020)
The purpose of this research is to describe the implementation of curriculum modification in components of purpose, content, process, and evaluation of the subjects of natural sciences (IPA) in class VI SD 1 Trirenggo Bantul. This type of research is qualitative descriptive research. Data collection techniques are performed with observations, interviews, and documentation. The data analysis technique used is the Miles and Huberman model by using data collection, data reduction, data display, and conclusion drawing/ verification. The results showed that modification of the curriculum of science subjects in class VI SD 1 Trirenggo Bantul on components of objective aspects of basic competency has not been modified and indicator aspects have been modified. The components of the content of science?s lesson have not been modified or have not adjusted with the ABK (children with special needs). In the components of the teaching process, the teaching techniques, environment/settings of learning, and learning time have been modified and aspects of teaching methods, learning media, and learning resources have not been modified. On the evaluation components, aspect of evaluation time, the evaluation technique, place of evaluation, approval criteria, and the class upgrade system have been modified and aspects of the test, the form of results, and the form of diploma have not been modified.